Comparison of Cemented and Non-cemented Allografts in Dogs with Osteosarcoma - Kirpensteijn, J.; Steinheimer, D.; Park, R. D.; Powers, B. E.; Straw, R. C.; Endenburg, N.; Withrow, S. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
This study compares the radiographic and histological appearance of cemented and non-cemented massive cortical allografts in dogs that underwent a limb sparing procedure for osteosarcoma of the distal radius. Treatment consisted of removal of the affected bone and pancarpal arthrodesis using non-cemented (n = 13) or cemented (n = 47) fresh-frozen allografts. Allografts were evaluated using a radiographic and histological scoring system and compared statistically between groups. Allografts with better healing received a higher radiographic score and a lower histological score. The mean radiographic scores, for proximal union and distal union, were significantly greater in the non-cemented group at most evaluation periods. Complications after the operation included screw, plate, allograft and host bone failure, infection and local tumour recurrence. Screw failure in the allograft and allograft failure were significantly more common in the non-cemented group. Histological examination was performed on 44 dogs and cement increased the mean combined histological scores, and mean healing scores of the distal host-graft interface significantly. The use of cemented allografts significantly decreases complications associated with implant loosening or allograft failure but may slightly delay allograft healing. At this point, the clinical relevance of the delay in healing is questionable and the benefits of intramedullary PMMA would appear to outweigh this relative delay in healing.This study evaluated 60 radial allografts after limb sparing procedures using a standardized radiological and histological scoring system. The use of cemented allografts significantly decreased complications associated with implant loosening or allograft failure but may slightly delay allograft healing.
Keywords: Dog; limb sparing; allograft; polymethylmethacrylate; bone healing; osteosarcoma